Code Mixing In Jerome Youtube Videos - Desi Arintawati; Aris Hidayatulloh; Abdul Ayiz (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The phenomenon of code mixing is not only found in society, but also on social media such as YouTube. One of the YouTubers in Indonesia who often uses code mixing is Jerome Polin. Jerome Goes to School is one of the contents in his YouTube video, in that content he uses code mixing to communicate with his interlocutors or his audience. Code mixing has three types, namely, insertion, alternation, and congruent lexicalisation. The purpose of this study is to identify the types of code mixing used in Jerome Polin's utterances. This research uses Muysken's (2000) theory to analyse the types of code mixing. The data source for this research was taken from a video on Jerome's YouTube channel called Nihongo Mantappu. The data comes from Jerome Polin's utterances in YouTube content videos. Researcher investigate two data videos from the youtube channel. The first video is entitled Kaget! Di Kampus Ada Stadium!? Keliling Univ No.1 Taiwan(NTU)| Goes to School. The second video is Akhirnya!! Wasedaboys Ke Cambridge University! Campus Tour Naik Kapal!? | World Trip 6. This research uses descriptive qualitative method, the researcher collected data, made analyzes, and made conclusions. The results of this study found a total of 74 code mixing data. The most common type found is insertion and the least type is alternation. Insertion was found 69 (93.24%) data, alternation 1 (1.35%) data, and congruent lexicalisation 4 (5.41%) data.